1997
DOI: 10.1159/000139535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trilinolein on Superoxide Dismutase Activity and Left Ventricular Pressure in Isolated Rat Hearts Subjected to Hypoxia and Normoxic Perfusion

Abstract: Oxygen-derived free radicals have been implicated in the development of myocardial injury during hypoxia/reperfusion. Antioxidants can effectively inhibit the formation of free radicals and ameliorate the myocardial damage which may occur during hypoxia/reperfusion. Trilinolein is a triacylglycerol recently purified from the traditional Chinese medicinal plant Panax pseudo-ginseng. It has linoleic-acid residues as the only type of fatty acid residue in all three esterified positions of the triacyglycerol. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Recent evidence suggests that ROS, such as superoxide anions and hydrogen peroxide, may play a role as intracellular second messengers regulating the transcription of SOD [23]. In the previous reports from our laboratory, we found that SOD gene expression and activity also can be regulated by other antioxidants, such as catechin [21] and trilinolein [24]. These results implicated that the antioxidant effect of ascorbate in the present study may be one of the major mechanisms related to SOD changes.…”
Section: Discussionsupporting
confidence: 82%
“…Recent evidence suggests that ROS, such as superoxide anions and hydrogen peroxide, may play a role as intracellular second messengers regulating the transcription of SOD [23]. In the previous reports from our laboratory, we found that SOD gene expression and activity also can be regulated by other antioxidants, such as catechin [21] and trilinolein [24]. These results implicated that the antioxidant effect of ascorbate in the present study may be one of the major mechanisms related to SOD changes.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to that of ·-tocopherol, trilinolein was previously reported to produce an antioxidant activity in a concentration-dependent manner [5]. In rat hearts pretreated with 0.1 ÌM trilinolein and subjected to 60 min of hypoxia, Cu,Zn-SOD activity was increased compared with baseline or with hearts subjected to 60 min of hypoxia without trilinolein [6]. In addition, it has been reported that pretreatment with trilinolein appeared to be associated with better preservation of left ventricular function during hypoxia and a more rapid return to recovery during the subsequent normoxic perfusion.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, it has been reported that pretreatment with trilinolein appeared to be associated with better preservation of left ventricular function during hypoxia and a more rapid return to recovery during the subsequent normoxic perfusion. [6]. A previous study has also demonstrated that myocardial protective effect of trilinolein could be related to its antioxidant effect via potentiation of SOD, particularly Cu,Zn-SOD, during hypoxia [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Role of OFRs in myocardial injury caused by ischemia/reperfusion is apparent [5,6]. Activation of the complement system, generation of chemotactic peptides, migration and activation of polymorphonuclear cells, OFR-induced changes of membrane and lipid, and depletions of intracellular scavengers of free radicals may be involved in reperfusion injury [7]. The involvement of a superoxide radical and oxidized lipids in vessel-wall abnormalities has also been introduced in atherogenesis [4].…”
Section: Introductionmentioning
confidence: 99%